Knowledge development of tweens in RE - the importance of school class and communication - Osbeck, Christina (British Journal of religious education, 2019)
This article draws on empirical findings from an religious education (RE) test done by 52 pupils in three different classes on two occasions at the beginning and end of the 2011/2012 academic year. The purpose is to examine whether RE knowledge development can be identified generally, whether there are differences between classes, and if so whether they can be related to communication patterns and describe directions of knowledge development within RE. A sociocultural perspective on learning is used, stressing the importance of communication and the discursive practices the individual is a part of for what is learnt. The findings show that RE developments over the course of the academic year can be identified in all three classes, and that there are differences among the classes in both achievement levels and developments, indicating variety in the degree to which the discursive practices of the classes facilitate RE learning. Among the individual communicative factors, 'asking questions' when one is curious or does not understand shows to be one important factor. The greatest developments seem to be among less complex and learning-about forms of RE knowledge.